Chronic nasopharyngeal and otitis media tuberculosis: diagnosis and management difficulties. Issue 8 (25th August 2022) - Pais, José Pedro; Caçador, Maria; Mourato, Teresa; Paço, João
Abstract : Nasopharyngeal and otitis media tuberculosis are rare extrapulmonary manifestations of Mycobacterium tuberculosis infection. We present a case of a middle-aged woman with manifestations of both conditions along with a description of the anatomical and temporal evolution of the disease. This case also highlights the difficulty of diagnosis and management of this condition, requiring a multidisciplinary approach. Extrapulmonary tuberculosis must be considered in the differential diagnosis of multiple head and neck conditions, including refractory chronic rhinosinusitis and otitis.